Castle Hangnail - Vernon, Ursula (Dial Books for Young Readers, an imprint of Penguin Group (USA) Inc., 2015)
When little, twelve-year-old Molly arrives at Castle Hangnail to fill the vacancy for a wicked witch, the minions who dwell there have no choice but to give her the job and at first it seems she will be able to keep the castle open, but Molly has quite a few secrets that could cause trouble.